Experimental Study on Immersion Effects of Pressure Water on the Tensile Characteristics of Sandstone Samples. (1st February 2021) - Yin, Dawei; Chen, Shaojie; Chen, Bing; Liu, Rui; Li, Faxin
Abstract : In this study, Brazilian splitting tests were conducted on sandstone samples subjected to drying and immersing at water pressures of 0, 1, and 3 MPa (immersion duration of 120 h). Investigation of the immersion effects of pressure water on the tensile characteristics of the samples revealed that their tensile strengths decreased with the immersion water pressure. Relative to a sandstone sample subjected to drying alone, immersing at water pressures of 0, 1, and 3 MPa reduced the tensile strength by 12.96%, 19.03%, and 30.16%, respectively. Although the immersed samples experienced splitting failure indicative of obvious brittle failure characteristics, decreases in the postpeak stress reduction rate with immersion water pressure revealed that the intensity of brittle failure weakened with pressure. Based on the obtained data, the deformation evolution process of the sandstone samples could be divided into five stages: deformation adjustment, formation of local deformation zones, local deformation zone propagation, failure surface formation, and sample failure. The water pressure aggravated the physicochemical reactions between water and the hydrophilic minerals in the sandstone, promoting argillisation, dissolution, and loss of hydrophilic minerals and interparticle cementitious materials. As a result of these immersion micromechanisms, the deterioration of the sandstone samples increased with the immersion water pressure, with the average porosities of the fracture surfaces at 0, 1, and 3 MPa increasing by 142.86%, 368.37%, and 593.88%, respectively, relative to the dried sample. As a result of these morphological changes, the sandstone samples subjected to water pressure immersion failed at small axial stresses with low levels of applied mechanical energy.